Negative Differential Resistance in ZnO Nanowires Bridging Two Metallic Electrodes - Lee Ching-Ting; Zhang Yang (Nanoscale Research Letters, 2010)
Abstract The electrical transport through nanoscale contacts of ZnO nanowires bridging the interdigitated Au electrodes shows the negative differential resistance (NDR) effect. The NDR peaks strongly depend on the starting sweep voltage. The origin of NDR through nanoscale contacts between ZnO nanowires and metal electrodes is the electron charging and discharging of the parasitic capacitor due to the weak contact, rather than the conventional resonant tunneling mechanism.